Design and Experiment of a Three Phase Two Switches Voltage Clamping Buck PFC. Issue 5 (14th February 2023) - Zhao, Yinfeng; Yu, Fei; Song, Qingguo; Zhu, Zhongni
Abstract : A new three‐phase two‐switch voltage clamping buck Power Factor Correction (PFC) is presents in this paper. The principle and equations of operations are described in detail. Based on the volt‐second balance principle of input inductance in the new converter, this paper gives the design method of the circuit's key components, with voltage and current stresses analyzed. On the basis of the theory above, a prototype with parameters of a 5 kW is designed. Problems of extremely high switch peak voltage stress in the conventional one are solved. The manufacturing cost of high power three phase rectifier has been significantly decreased. A 5 kW experimental prototype with unity power factor, 4.4% input line current THD, 200 Vdc output, and system efficiency of 96% at full load under 380 Vrms input line‐to‐line voltage has been successfully implemented. © 2023 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.